1970
DOI: 10.4188/jte1955.16.216
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on the Biaxial Tensile Properties of Single Tricot Warp Knitted Fabric with Open Lap

Abstract: The biaxial tensile properties of single tricot warp knitted fabrics v ith an open lap have been calculated theoretically by developing the analysing method used on the close lap structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Thus, once m is known, equation ( 1) can be used to determine whether interyarn slippage occurs. The range of m for yarn-to-yarn friction is approximately (Yanagawa et al, 1970). If the ratio on the left-hand side of equation ( 1) is high relative to m, the interlacing yarns are likely to slip during fabric extension.…”
Section: 3/4mentioning
confidence: 99%
“…Thus, once m is known, equation ( 1) can be used to determine whether interyarn slippage occurs. The range of m for yarn-to-yarn friction is approximately (Yanagawa et al, 1970). If the ratio on the left-hand side of equation ( 1) is high relative to m, the interlacing yarns are likely to slip during fabric extension.…”
Section: 3/4mentioning
confidence: 99%
“…Most of these investigations were based on plain weft-knitted structure and a single loop was used as a unit cell for analysis. 11 Yanagawa and colleagues 12,13 developed the analytical method for calculation of the tensile properties of single tricot warp knitted fabrics, but it is limited to biaxial stress of knitted fabric from conventional yarn.…”
Section: Introductionmentioning
confidence: 99%
“…z Two geometrical studies have been reported, one by Grosberg [5], who considers double bar closed lap structures, and another by Yanagawa et al [ 19,20] who examine single bar fabrics. These models possess the usual limitations arising from geometrical fabric models and make physically unrealistic assumptions about the nature of yam contact and fabric thickness effects.…”
mentioning
confidence: 99%